Modeling polarity buildup and cell fate decision in the fly eye: insight into the connection between the PCP and Notch pathways. - Le Garrec, J.F.; Kerszberg, M. (Development genes and evolution, 2008)
Metazoan development critically depends on a surprisingly short list of conserved pathways. How can such ubiquitous systems regulate a variety of cell-biological events at various developmental stages in different tissues and in different organisms? In the fruit fly, the planar cell polarity (PCP) pathway regulates widely different processes. It is known to be involved in the correct alignment of hairs on the wing and in the determination of R3/R4 photoreceptor cell fates in the eye. In the wing, PCP regulates the spatial structure of cells sharing the same transcriptional fate, while in the eye the Notch signaling pathway has been recruited to additionally transduce the PCP signal to the nuclei in the two differentiating members of a photoreceptor pair. We have recently proposed a computational model for PCP in the wing; this model posited, on the basis of all known data, that planar polarity buildup is driven by asymmetric molecular complexes constructed around the cadherin Flamingo and spanning the space between two cells. In this paper, we show that the same model, combined with a novel Notch module, equally applies in the eye. The model provides insight into the crosstalk between the PCP and Notch modules in development and illustrates the ability of signaling modules to robustly maintain vital phenotypes in a noisy environment.